Tracking of ships navigation in the Strait of Malacca using automatic identification system - Jaswar, Koto (Taylor & Francis Group, 2014)
The Strait of Malacca received special attention in the United Nations Convention on the Law of the Sea (UNCLOS) because of the economic, navigational safety and other vital importances to the international shipping community and the navigation of local vessels. IMO concerns about safety of ship navigation by the endorsement legal issue of the Automatic Identification System (AIS) for tracking ships to avoid collision from the loss of lives and property. In 2002, the AIS was made compulsory for most large commercial ships of 300 gross tonnage and above engaged on international voyages, cargo ships of 500 gross tonnage and above not engaged on international voyages and passenger ships irrespective of size. This paper discusses tracking of ship navigation in the Strait of Malacca using the AIS which was developed in Marine Technology Center (MTC), Universiti Teknologi Malaysia (UTM). The UTM-AIS consists of two receivers of SRI161 and FA30. The detail data of ships recorded by the UT-AIS are analyzed using Marine Safety and Environment simulation developed using Visual Basic 2010. The results of the study show that daily 1500 vessels approximately pass through the Strait of Malacca with 32 percent of Liquid bulk, 11 percent of container ships and 42 percent under Singaporian flag.